Statistical Modeling And Optimization Of Process Parameters For 2,4-Dichlorophenoxyacetic Acid Removal By Using Ac Pdmaema Hydrogel Adsorbent Comparison Of Different Rsm Designs And Ann Training Methods - Fadzil, Haiekal Mustaqim Mohd (Universiti Sains Malaysia, 2022)
In this study, an attempt was made to create hydrophobic fabric using a straightforward immersion procedure. In order to generate adequate roughness with hydrophobic surface chemistry, cotton fabric was coated with titania nanoparticles made from Ti(IV)-isopropoxide (TTIP). After that, the aminopropyltriethoxysilane (APTES) treatment was applied to the coated textiles in order to lower the surface energy. We looked at how coating modified cloth with TiO2 and APTES affected its surface morphology and how hydrophobic it was. Scanning electron microscopy (SEM), energy dispersive X-ray (EDS), and Fourier transform infrared (FTIR) spectroscopy were used to evaluate the shape of hydrophobic fabric as well as its composition. The findings indicated the production of asymmetrical layers of TiO2 NP and APTES throughout the entirety of the surface of the fabric. An investigation into the hydrophobicity of fabrics using the water contact angle (WCA) measurement revealed that the modified fabric exhibited excellent water repellence. In addition to that, the focus of this work is on the adsorption of oil onto TiO2-APTES fabric for the purpose of removing oil from an oil-water solution. This finding provided proof that the adsorbent was capable of absorbing oil and that various parameters had an effect on the adsorptive capability of the adsorbent. The weight of the adsorbent has a direct correlation to the percentage of oil that is removed, whereas the concentration of the adsorbate has the opposite effect. The oil removal percentages, on the other hand, are not impacted by the contact time. According to the results of equilibrium tests, the Langmuir isotherm was the most appropriate model to describe oil removal by TiO2-APTES fabric. Research was also done on the reusability of the adsorbent, which was shown to be recyclable up to five times.